FAKTOR DAN STRATEGI PENGEMBANGAN BUDAYA BACA MELALUI MEMBACA PEMAHAMAN MAHASISWA - NFN Pranowo; Antonius Herujiyanto (Masyarakat Linguistik Indonesia, 2015)
A reading habit can be defined as one’s attitude, behaviour, and mind-set patterns in reading which has been strongly rooted and unchangeable. Indonesians’ reading habit is still low. According to the 2009 research conducted by the Economic Co-operation Developing Organization [OPKE], the reading interest index of Indonesian people is the lowest among that of 52 East Asian countries. Similarly according to the 2012 data from UNESCO, the Indonesians’ reading index is 0,001, which means that there is only one out of 1000 Indonesians who is interested in reading. This study aims to describe many different factors affecting the reading comprehension skills and strategies which are in line with those efforts to develop the student’s reading habit. The subjects of the research are the fifth semester students of 2015/2016 academic year of the Department of Language (Indonesian) of USD and UST Yogyakarta. The data are the questionnaire results on the factors of reading comprehension competency and reading habit strategy developing model. The findings reveal that there are two factors which affect one’s reading comprehension competency, namely, internal and external factors, and the appropriate reading habit strategy developing models are K-W-L (Know-Want-Learnt) and MURDER (Mood-Understand-Recall-Digest-Expand-Review).